Social Defeat Stress in Adolescent Mice Induces Depressive-like Behaviors with Reduced Oligodendrogenesis. (1st September 2020) - Shimizu, Takeshi; Ishida, Akimasa; Hagiwara, Mutsumi; Ueda, Yoshitomo; Hattori, Atsunori; Tajiri, Naoki; Hida, Hideki
Highlights: Social defeat stress to adolescent mice causes depressive-like behaviors. Oligodendrogenesis is reduced by social defeat stress in adolescent mice. Clemastine administration promotes oligodendrogenesis in socially defeated mice. Clemastine treatment rescued depressive-like behaviors caused by social defeat stress during adolescence. Abstract: Strong stress related to adverse experiences during adolescence can cause mental disorders, as well as affecting brain structure and function. However, the underlying neurobiological mechanisms remain largely unknown. To investigate whether stress induced by adverse experience during adolescence affects oligodendrocyte (OL) remodeling, social defeat stress was applied to 6-week-old adolescent mice for 10 days, followed by behavioral tests and assessments of oligodendrogenesis. Socially defeated mice showed depressive-like behaviors in behavioral experiments. Stress led to a decrease in the number of newly born OLs in the anterior cortical region and the number of proteolipid protein-positive mature OLs in the corpus callosum and posterior cerebral cortex. Fewer bromodeoxyuridine-incorporated CC1-positive mature OLs were observed in these regions in socially defeated mice. To assess whether decreased oligodendrogenesis caused by social defeat stress is related to depressive-like symptoms under stress, clemastine, a drug that induces OL generation, was administered to socially defeated adolescent mice, resulting in the rescue of the behavioral abnormalities accompanied by increased oligodendrogenesis. These findings suggest that oligodendrogenesis in adverse environments during adolescence plays a role in psychiatric disorders, and clemastine may provide a potential therapeutic drug for adolescent mental disorders, targeting OLs.